Development of technology of project management and balanced system of indicators: foreign experience and Kazakhstan practice (Journal of Economic Research & Business Administration, 2015)
Transfer process to the Republic of Kazakhstan of management technology by projects and the instruments of realization of company strategy– the balanced scorecard in the last decade is considered at the article. Comparison of development of these administrative approaches in Kazakhstan with foreign practice shows that project management chronologically anticipated practically all modern approaches of management by company development in the developed countries in the period of the second half of the 20th century. Project management, thus, actively promoted introduction in business of these new instruments of modernization of enterprise.In Kazakhstan attempt of introduction of the balanced scorecard took place when project management wasn't adequately mastered yet by managers and heads of the organizations that led to a weak demand of the tool which is successfully applied in civilized countries.At the same time, simultaneous introduction in activity of the Kazakhstan companies project management and balanced scorecard can be quite solved task and even to have synergetic effect if to carry out development of a company through projects. This technology includes identification of key problems of development of the company, formation of a strategic objective of development on four aspects of balanced scorecard, definition on their basis of key objects of activity of the company, creation of structure of management of them and development of information system of monitoring of conditions of these objects of activity.
Keywords: project management; balanced scorecard; management of company development; standards of project management; company modernization